Constitutional and European legal rules for armaments’ quality and presentation of alternative procurement: Contribution to the possibilities of contractual optimisation in armament procurement (the contract as a force multiplier) - Gimmler, Karl-Heinz (European Integration Studies, 2024)
War is a legally relevant hazardous situation with potentially incalculable human casualties in terms of life and limb, especially of the soldiers in action. This dangerous situation is comparable to a nuclear power plant meltdown. Many European states have a constitutional obligation (not examined in detail). For example, the Federal Republic of Germany and Austria must qualitatively optimise armament for the purpose of protecting the fundamental rights of soldiers who may be fighting. This obligation exists throughout the EU based on the CFR and the jurisdiction of ECHR, in the rank of ordinary statutory law. Armament procurement is also a legal subject for multidimensional optimisation under numerous legal aspects, in particular the choice of contract type, price optimisation, and tax optimisation. Therefore, it should (finally) be considered multidimensionally for the benefit of the defence of freedom in EU-Europe and NATO as a whole. The procurement of defence equipment must contractually enable the core objectives of the state, namely secure availability, sustainable defence equipment, and cost-effective procurement. To this end, hundreds of individual contractual clauses and regulations must be used. Rental and leasing contract procurement is generally more cost-effective and otherwise offers no disadvantages compared to traditional purchase procurement. All conceivable disadvantages can be contractually prevented and avoided. Specific unavoidable disadvantages are practically not recognisable. It is a suitable “force multiplier and defence enabler.” Optimised contractual arrangements, particularly other contract types and VAT optimisation, can save at least tens of billions of euros per year in the whole EU-Europe. Due to the lower impact on the annual budget, more and/or better quality of armaments can be procured.